An immunomodulatory role for CD4+CD25+ regulatory T lymphocytes in hepatitis C virus infection - Cabrera, Roniel; Tu, Zhengkun; Xu, Yiling; Firpi, Roberto J.; Rosen, Hugo R.; Liu, Chen; Nelson, David R. (Hepatology (Baltimore, Md.), 2004)
The CD4+CD25+ regulatory T lymphocytes have been implicated in suppressing T cell immune responses. Our aim was to characterize the frequency, phenotype, function, and specificity of CD4+CD25+ T cells in hepatitis C virus (HCV) infection. Peripheral CD4+CD25+ cells from recovered (n = 15), chronic infected (n = 30), and normal control (n = 15) subjects were analyzed ex vivo for quantitation, phenotype, and effect on HCV‐specific interferon gamma production and proliferation. CD4+CD25+ specificity was determined by intracellular cytokine staining for interleukin 10 (IL‐10). A higher proportion of CD4+CD25+ were found in chronic infection (mean, 3.02%) when compared with recovered (1.64%, P = .001) and normal controls (2.27%, P = .02). CD4+CD25+ cells display CD45ROhigh, CD45RAlow, CD28high, CD62Lhigh, and CD95high phenotype. HCV‐specific interferon gamma activity was enhanced in peripheral blood mononuclear cells depleted of CD4+CD25+ and suppressed in peripheral blood mononuclear cells enriched with CD4+CD25+. Depletion of CD4+CD25+ cells also enhanced HCV‐specific CD4+ and CD8+ T cell proliferation. Cytokine analysis suggested CD4+CD25+ cells secrete transforming growth factor beta (TGF‐β1) and IL‐10. The inhibitory role for TGF‐β1 was confirmed by anti–TGF‐β1. Transwell studies showed CD4+CD25+ mediated suppression to be dose dependent and requiring cell contact. CD4+CD25+ cells showed HCV‐specificity through IL‐10 production, with a frequency ranging from 1.9% to 5.3%. A positive correlation was detected between CD4+CD25+ T cell frequency and HCV RNA titer, whereas an inverse relation was found with liver inflammatory activity. In conclusion, CD4+CD25+ T lymphocytes constitute a highly differentiated population and appear to play a role in viral persistence by suppressing HCV‐specific T cell responses in a cell–cell contact manner. (HEPATOLOGY 2004;40:1062–1071.)